Reduced blood pressure after smooth muscle EFNB2 deletion and the potential association of EFNB2 mutation with human hypertension risk - Woodward, M; Wang, Y; Hamet, P; Thorin, E (Nature Publishing Group, 2016)
Ephrin B2 (EFNB2) is a ligand for erythropoietin-producing hepatocellular kinases (EPH), the largest family of receptor tyrosine kinases. It has critical functions in many biological systems, but is not known to regulate blood pressure. We generated mice with a smooth muscle cell-specific deletion of EFNB2 and investigated its roles in blood pressure regulation and vascular smooth muscle cell (VSMC) contractility. Male Efnb2 knockout (KO) mice presented reduced blood pressure, while female KO mice had no such reduction. Both forward signaling from EFNB2 to EPHs and reverse signaling from EPHs to EFNB2 were involved in regulating VSMC contractility, with EPHB4 serving as a critical molecule for forward signaling, based on crosslinking studies. We also found that a region from aa 313 to aa 331 in the intracellular tail of EFNB2 was essential for reverse signaling regulating VSMC contractility, based on deletion mutation studies. In a human genetic study, we identified 5 SNPs in the 3’ region of the EFNB2 gene which were in linkage disequilibrium and which were significantly associated with hypertension for male but not female subjects, consistent with our findings in mice. The coding (minor) alleles of these 5 SNPs were protective in males. We have thus discovered a previously unknown blood pressure-lowering mechanism mediated by EFNB2 and identified EFNB2 as a gene associated with hypertension risk in humans.